1991
DOI: 10.1002/hep.1840130318
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic preservation of hepatocytes. III. Effects of resuspension media on viability after up to 7 days of storage

Abstract: Hepatocyte suspensions provide a rapid method to determine how hypothermic storage affects liver cell metabolism and viability. Using these studies, improved methods of hypothermic liver preservation for transplantation may be developed. In this study, rat hepatocytes were cold-stored for up to 7 days in University of Wisconsin liver preservation solution. At the end of each day of storage hepatocytes were resuspended in Krebs-Henseleit buffer or tissue-culture medium (Liebovitz-15; Fischer's; modified Fischer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…In most studies, cell viability in suspension is assessed directly after cold storage or after a short rewarming phase in suspension [27], [28], [29]; although this parameter is very insensitive, loss of cell viability has been described to occur after 24–120 h. Compared to adherent rat hepatocytes [6], rewarming injury was not very pronounced in cell suspensions in the current study. Furthermore, since the crude cell suspension was used for the experiments, cell death during rewarming is likely to be partly due to cell damage already initiated during the cell isolation process.…”
Section: Discussionmentioning
confidence: 71%
“…In most studies, cell viability in suspension is assessed directly after cold storage or after a short rewarming phase in suspension [27], [28], [29]; although this parameter is very insensitive, loss of cell viability has been described to occur after 24–120 h. Compared to adherent rat hepatocytes [6], rewarming injury was not very pronounced in cell suspensions in the current study. Furthermore, since the crude cell suspension was used for the experiments, cell death during rewarming is likely to be partly due to cell damage already initiated during the cell isolation process.…”
Section: Discussionmentioning
confidence: 71%
“…This solution is responsible for the longest period of safe preservation of isolated cells, particularly in pancreatic islets and hepatocytes. 15,16 Animal studies have confirmed the efficacy of using UW solution for preservation of fasciocutaneous flaps. 17,18 Some authors have hypothesized that lactobionate is the key component of the UW solution.…”
Section: Discussionmentioning
confidence: 95%
“…A favored approach to the storage of cells is hypothermic preservation 1, 55, 56. Among the advantages of this storage method is that it does not require special equipment for preservation and might allow shipping to remote sites for transplantation.…”
Section: Discussionmentioning
confidence: 99%